Synthesis of Mesoporous Ce1-xSmxO2 Solid Solution Materials and its Catalytic Performance - Yu, Lei; Chen, Feng; Qian, Jun-Chao; Liu, Cheng-Bao; Chen, Zhi-Gang (Asian Journal of Chemistry, 2014)
Novel mesoporous structural Ce1-xSmxO2 solid solution materials have been synthesized via a facile approach of evaporation-induced self-assembly (EISA) in the presence of nitrate as inorganic species and triblock copolymers P123 as template. The detailed charaterization by power X-ray diffraction, transmission electron microscope, selected electron diffraction revealed the samples possessing fluorite-structure with the average grain size of 7 nm. Furthermore, N2 adsorption-desorption measurement illustrated the particular hierarchical porous textural Ce1-xSmxO2 solid solution with the pores size in diameter between 2 to 4 nm and the maximun surface area of 106 m2/g. The temperature-programmed reduction of H2 (H2-TPR) result confirmed that the ceria-samarium solid solution owned more vacancies than pure CeO2, hence the double level pores textural Ce1-xSmxO2 seem to be potential candidates for catalytic aspect.